Analisis Kontrastif Proses Morfofonologi Bahasa Jawa dan Bahasa Arab - Amrulloh, Muhammad Afif (Arabiyatuna : Jurnal Bahasa Arab, 2018)
Mastery of a foreign language is very important. The increasingly close relations between nations requires the availability of foreign language skills to meet communication needs. Moreover, there are often difficulties or difficulties experienced by foreign language learners with a mother tongue background who have a language system that is not the same as a foreign language system. The purpose of knowing the process morfofonemik in the Java Language and the Arabic language. Types of library research or library research, which takes a data source in the literature. This study includes the type of qualitative research. The research explained the data and then analyzed systematically. The results and findings of the study that the process of morphophonology in the Java language occur because of the appearance of phonemes, pelesapan phonemes, leaching phonemes and shifting phonemes. Whereas in Arabic occurs phonemeal dissolution, phoneme changes, the addition of phonemes and shifting phonemes. The equation of the process morfofonemik between the two languages, namely the same-the same happened phoneme dissolution, while the difference is in the Arabic language does not occur appearance and leaching phonemes as in the language of Java. Implications this study has contributed to the ease of learning in the mastery of foreign languages by learners of a foreign language, namely Arabic.